Model Pembelajaran POE (Predict-Observe-Explain) Terhadap Keterampilan Berpikir Kritis Siswa SMP Miftahul Khair NW Kabupaten Lombok Tengah - Sofian Azhari; Nining Purwati; Alwan Mahsul; Bq Siti Maulida Azmi; Juwita Lestari (Otus Education: Jurnal Biologi dan Pendidikan Biologi, 2023)
This classroom action research aims to improve students' critical thinking skills through the application of the POE (predict-observe-explain) learning model. The study was conducted in two cycles with a total of six meetings. Each cycle consists of planning, action, observation, and reflection. The subjects of this study were the 8th-grade students of Miftahul Khair Islamic Junior High School, Central Lombok. The data collected were students' critical thinking skills and the activity of the POE (predict-observe-explain) learning model implementation namely teacher activities and student activities. The instruments used were critical thinking test instruments and observation sheets for the implementation of the POE learning model (predict-observe-explain). The research data were analyzed by comparative descriptive. The results showed that the application of the POE (predict-observe-explain) learning model could improve students' critical thinking skills, as evidenced by the average student's critical thinking skills which increased from an average score of 41 in the moderate.